Assessment of Nurses’ knowledge about Enteral Feeding at Critical Care Units in Hospitals of Al-Anbar Governorate - Abdulrahman Thiab Ahmed; Huda Baker Hassan (Iraqi National Journal of Nursing Specialties, 2022)
Objectives of the study: The present study aims to evaluate nurses’ knowledge about enteral feeding in critical care units. Methodology A descriptive study design was carried out in the critical care units at Al-Ramadi Teaching Hospital and Al-Fallujah Teaching Hospital of Al-Anbar Governorate for the period 6th of December 2020 to 5th of January 2021. A non-probability (purposive sample) consists of 32 nurses was selected based on the study criteria. The instrument consist of, the reliability of instrument was = 0.87. The instrument consist of 30 items of knowledge about enteral feeding, the first part, included the study sample’s socio-demographic characteristics of age, gender, level of education, years of experience in nursing field, years of experience in critical care unit, and training course on enteral feeding, second part is a questionnaire to assess nurses’ knowledge about care provided to patients undergoing enteral feeding. Descriptive and inferential statistical analysis approaches were used for data analysis. Results: The findings of the study indicated that most of the nurses had fair level of knowledge about enteral feeding. Conclusions: The study concluded that most of critical care nurses did not have a good knowledge about enteral feeding and this can lead to inadequacy of calorie intake in critically ill patients. Recommendations: The study recommends developing and improving the nurses’ knowledge about the correct method of enteral feeding through education program and participation in training course programs about safe administration of enteral feeding.